PERAN DIET DALAM MIKROBIOTA SALURAN CERNA PADA PASIEN KANKER KOLON: SYSTEMATIC REVIEW - Alifa Bestari, Salwa; Ahmi Albanna, Wildan (Jurnal Kesehatan dan Pembangunan, 2025)
One cancer form that is rather common in Indonesia is colon cancer. Diet is one of the risk factors for the development of cancer. In this instance, the formation of cancer cells, particularly colon cancer, is significantly influenced by the gastrointestinal microbiome. If the proper diet is not followed, the gut flora may become dysbiotic. A disorder known as dysbiosis occurs when the gastrointestinal microbiota is out of equilibrium. Long-term exposure to this will have an impact on human health in general. One of the beneficial bacteria that can influence someone's health is Bifidobacterium species. This comprehensive study aims to determine how food affects Bifidobacterium spp. bacterial abundance and how it affects the development of